ZnO nanoparticles for anti-corrosion nanocoating of carbon steel - J.N., Hasnidawani; H. Noor, Azlina; Hassan, Norita; Samat, Noorasikin; Bonnia, Noor Najmi; Surip,, Siti Norasmah (Trans Tech Publications, Ltd., 2017)
Nanostructured coatings offer great potential for various applications due to their superior characteristics that are not typically found in conventional coatings. This research aimed at developing a new and improved coating that employs zinc oxide nanopowder as the agent to achieve corrosion resistant properties for a coating. The research project discusses on its corrosion behaviour of epoxy-zinc oxide in different media by measuring its corrosion rate. Mild carbon steel was used as the substrate for the epoxy-zinc oxide coating. The corrosion behavior mechanism of mild steel was investigated in different media, namely fresh water, NaCl solution, HCl solution and NaOH solution. Immersion test was conducted and studied for a period of 60 days, with daily and weekly weighing and immersing. The corrosion rate was calculated and mild steel corrodes in the different environment and degrades in the following trend; HCl → NaCl → NaOH → H2O.